Samsung Malaysia Electronics Sdn. Bhd. / Muhammad Hakimi Ahmad - Ahmad, Muhammad Hakimi (2022)
Samsung Malaysia Electronics Sdn Bhd is a South Korean multinational corporation that specializes in consumer electronics, semiconductors, memory, technological equipment, and, most notably, Samsung Galaxy smartphones. According to historical data, the company has been successful in developing its business by exporting to over 100 nations in regions such as Asia, the Middle East, Europe, and Oceania. The focus of this case study analysis is on the Samsung keyboard, which will be analysed, investigated, and identified, as well as their current problems, to find a better solution that can be adopted in the Samsung firm to improve the existing system in business development growth. Samsung is a Malaysian electronics company that produces a variety of products, including keyboards. Customers of a wide age range and technological gurus are the company's target markets. Sony, Apple, LG, Logitech, and other companies are among Samsung's competitors. In a nutshell, to compete in the global market, Samsung must develop more effective methods. As a result, the plan has undergone some examination and execution. Furthermore, a SWOT analysis has been drawn out to strengthen the company's strengths and to identify activities to address the company's weaknesses.